Acute toxicity of arsenic and oxidative stress responses in the embryonic development of the common South American toad Rhinella arenarum - Mardirosian, Mariana Noelia (2015)
Arsenic (As), a natural element of ecological relevance, is found in natural water sources throughout Argentina in concentrations between 0.01mg/L and 15mg/L. The autochthonous toad Rhinella arenarum was selected to study the acute toxicity of As and the biochemical responses elicited by the exposure to As in water during its embryonic development. The median lethal concentration (LC50) value averaged 24.3mg/L As and remained constant along the embryonic development. However, As toxicity drastically decreased when embryos were exposed from heartbeat-stage on day 4 of development, suggesting the onset of detoxification mechanisms. Given the environmental concentrations of As in Argentina, there is a probability of exceeding lethal levels at 1% of sites. Arsenic at sublethal concentrations caused a significant decrease in the total antioxidant potential but generated an increase in endogenous glutathione (GSH) content and glutathione S-transferase (GST) activity. This protective response might prevent a deeper decline in the antioxidant system and further oxidative damage. Alternatively, it might be linked to As conjugation with GSH for its excretion. The authors conclude that toad embryos are more sensitive to As during early developmental stages and that relatively high concentrations of this toxic element are required to elicit mortality, but oxidative stress may be an adverse effect at sublethal concentrations.